A Map Collection on the Internet - Crom, Wolfgang (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
The map department of the Württemberg State Library in Stuttgart started a new development for the representation of its collection. When the Internet became increasingly important as an additional means for libraries and librarians to collect and distribute information, we wanted to include our map collection. However, we not only wished to bring attention to its existence but also to create the possibility of presenting the main information about the maps.